Quelles organisations de la mobilité plus durables et moins dépendantes de la voiture dans les espaces ruraux à faible densité ? L’exemple du Parc naturel régional Loire-Anjou-Touraine - Marie Huyghe; Hervé Baptiste; Jean-Paul Carrière (Développement Durable et Territoires)
Two phenomena will in the next years hinder the rural populations’ mobility practices: the environmental recommendations of the French law “Grenelle 2”, which encourages the development of the most accessible areas only; the increasing cost of energy and fuel. In such a context, the excessive reliance on car for mobility is not a solution anymore: the poorly-served areas may then have to face a recessive dynamics, or even a new rural depopulation. This paper distinguishes three categories of population according to their mobility practices, and analyses four organizations of mobility in rural areas that could provide more sustainable mobilities, i.e. economically, socially and environmentally performant.